Translation Analysis of Morphological Process and Translation Techniques on Subtitle the Barbie Life in the Dreamhouse Series - Nike DwiAna; Raden Arief Nugroho (Yayasan Visi Intan Permata, 2024)
The aim of this research is to describe and identify the translation techniques, and morphological processes used, by translators in subtitle conversations of characters in web-series that translators use in subtitle conversations of main characters in films. This research focuses on translation and is qualitative in nature. Statements that have morphological elements and are the results of conversations with informants are the type of data used in this research. Utilizing the Morphology process by Yule (1996), data analysis is carried out simultaneously with the data collection process. The researcher concluded that translation techniques by Molina & Albir (2002) were used in the process of transforming the Source Language into the Target Language; In total, there are five morphological processes and 16 of the 18 translation techniques are used. Among the translation techniques, Linguistic Amplification is 16.46%, Literal Translation is 11.39%, for Borrowing (Pure and Naturalization), followed by Equivalence Determination, Generalization, and Variation with the same amount, namely 10.13%, Substitution 6.33%, Amplification followed by Linguistic Compression, and Particularization 5.06%, Compensation and Transposition also have the same results with 2.53%, Adaptation followed by Description, Discursive Creation, and Modulation with 1.27%. Affixation, there is a Suffix of 35.71%, and a Prefix of 7.14%. Non-Affixation includes Compounding 28.57%, Borrowing 14.29%, Acronyms 7.14%, and Clipping 7.14% all of which are morphological processes. Translation techniques and the Morphology process are appropriate strategies to be used as the first choice in analyzing the results of this research because they can produce significant contributions in a practical context. Based on the research findings, several practical implications can be identified, including the results of this research can help develop an understanding of the phenomenon under study. for a translator or related parties, providing guidance and recommendations to a translator in developing policy strategies or best practices in relevant fields. The researcher also concluded that translation techniques and morphological processes can be interrelated with the meaning conveyed.